Detection and isolation of Shiga toxin-producing Escherichia coli and microbial population counts on Argentinean Kosher beef for export to Israel = Detección y aislamiento de Escherichia coli productora de toxina Shiga y conteo de poblaciones microbianas en carne bovina Kosher argentina para exportar a Israel - Brusa, Victoria (2023)
The aim of this study was to provide data on the frequency of Top 7 Shiga toxin-producing Escherichia coli (STEC) and microbial population counts on processed beef from Argentinean Kosher cattle abattoirs authorized to export to Israel. A total of 480 samples (forequarters, primal cuts, trimmings) were taken and analyzed for Top 7 STEC detection and isolation and for mesophilic aerobic organism, coliform and E. coli enumeration. Differences in stx detection and microbial population counts on forequarter samples before and after salting were not statistically significant (P >0.05). All samples were negative for Top 7 STEC. Differences were significant for all microbial counts in primal cuts (P <0.001). Neck samples showed a higher level of contamination with the three groups of microorganisms than fore shank and brisket samples. The prevalence of stx was lower than that reported worldwide and in Argentinean export abattoirs. Salting did not significantly reduce the microbial load on forequarters.